Gender differences in triple jump phase ratios and arm swing motion of international level athletes - Panoutsakopoulos, V.; Theodorou, A. S.; Katsavelis, D.; Roxanas, P.; Paradisis, G.; Argeitaki, P. (Acta Gymnica, 2016)
Background: Female triple jumping is a relatively new athletics event. A limited number of researchers have focused on comparing male and female jumpers competing in international events, resulting in scarce findings in the literature regarding gender differences of the determinants of triple jump performance.